Maximizing annual yield of bifacial photovoltaic noise barriers. (1st March 2018) - Faturrochman, G.J.; de Jong, M.M.; Santbergen, R.; Folkerts, W.; Zeman, M.; Smets, A.H.M.
Highlights: A noise barrier with integrated bifacial photovoltaic modules is analysed. We developed a model for predicting the power output of bifacial PV systems. Excellent agreement was found between the modeled and measured power output. The effects of bifacial module orientation and tilt on the energy yield were studied. Abstract: In this work we consider noise barriers with integrated photovoltaic modules. The novelty is that bifacial modules are considered. A full scale bifacial photovoltaic noise barrier was built and its power output was monitored. In addition we developed an advanced numerical model for predicting this power output for given weather conditions. Excellent agreement was found between the measured power output and the model prediction. Next we used this model to demonstrate the effects of the orientation, tilt, location, cell position and bypass-diode configuration on the annual energy yield of bifacial photovoltaic noise barriers.